INFLUENCE OF PROCESSING METHODS ON THE PHYTOCHEMICAL, MINERAL AND FIBRE FRACTION OF JUJUBE FRUIT MEAL AS A POTENTIAL FISH FEED INGREDIENT - Yakubu, Hadiza B.; Bichi, Armayau H.; Dauda, Akeem B. (FUDMA JOURNAL OF SCIENCES, 2025)
Most of the ingredients used in fish feed preparation are extremely competitive since they are eaten by man and utilized in agro allied industry, hence costly. Consequently, effort concerning using plant materials that are not used by man received less attention. Ziziphus mauritiana is a common fruit that is found widely in numerous regions of the world. Hence this study examined some nutritional characteristics of raw and differently processed Z. mauritiana fruit meal as a potential ingredient in fish feed preparation. The fruit meal was processed by boiling, toasting, soaking and fermenting using standard methods. The processed meals were examined in triplicates for phytochemicals, minerals and fibre fractions. The results revealed that alkaloid was reduced significantly in boiling by 66.22% while toasting reduced the tannin level significantly (P
Keywords: Fibre fraction; Phytochemical; Processing methods; Jujube fruit